'Citizens' and 'Foreigners' in EU Law. Migration Law and its Cosmopolitan Outlook. Issue 3 (25th April 2016) - Thym, Daniel
Abstract: Migration has become a controversial subject across Europe and beyond. At the same time, the EU has built up an impressive set of rules for third‐country nationals over the past two decades, which—unlike the mobility of EU citizens—received comparatively little attention apart from immigration and asylum specialists. This contribution presents the constitutional framework for 'migration law' towards third‐country nationals and shows in how far they depart from the paradigm of intra‐European mobility. It will be argued that differences can be rationalised by divergent objectives and do, nonetheless, not present a move towards 'fortress Europe'. EU migration law maintains the distinction between citizens and foreigners at the same time as it protects migrants, including refugees. By accommodating migrants' rights and self‐government, EU migration law can be construed as an endeavour to replace traditional notions of alienage with constitutional rules with a cosmopolitan outlook.